Optical imaging of localized chemical events using programmable diamond quantum nanosensors - Rendler, Torsten; Neburkova, Jitka; Zemek, Ondrej; Kotek, Jan; Zappe, Andrea; Chu, Zhiqin; Cigler, Petr; Wrachtrup, Jörg (Nature communications, 2017)
Development of multifunctional nanoscale sensors working under physiological conditions enables monitoring of intracellular processes that are important for various biological and medical applications. By attaching paramagnetic gadolinium complexes to nanodiamonds (NDs) with nitrogen-vacancy (NV) centres through surface engineering, we developed a hybrid nanoscale sensor that can be adjusted to directly monitor physiological species through a proposed sensing scheme based on NV spin relaxometry. We adopt a single-step method to measure spin relaxation rates enabling time-dependent measurements on changes in pH or redox potential at a submicrometre-length scale in a microfluidic channel that mimics cellular environments. Our experimental data are reproduced by numerical simulations of the NV spin interaction with gadolinium complexes covering the NDs. Considering the versatile engineering options provided by polymer chemistry, the underlying mechanism can be expanded to detect a variety of physiologically relevant species and variables.
Keywords: Nanodiamonds; Nanotechnology; Microscopy, Confocal; Biosensing Techniques; oxidace-redukce; nanotechnologie; nanodiamanty; konfokální mikroskopie; biosenzitivní techniky; Optical Imaging; reprodukovatelnost výsledků; časové faktory; Quantum Theory; Reproducibility of Results; kvantová teorie; Hydrogen-Ion Concentration; transmisní elektronová mikroskopie; Oxidation-Reduction; Microscopy, Electron, Transmission; koncentrace vodíkových iontů; optické zobrazování; Time Factors